PROFIL SISWA DALAM MEMECAHKAN MASALAH MATEMATIKA BERDASARKAN GAYA KOGNITIF DAN GENDER - Mohammad Akbar; Cholis Sa'dijah; Sisworo Sisworo (FMIPA UNIVERSITAS NEGERI MALANG, 2020)
This purpose of the study is to s describe mathematic problem solving based kognitif style and gendre. This research with qualitative approach. The subject is a man student with field independent cognitif style (FIL) and a woman student with field independent cognitif style (FIP) and a man student with field dependent cognitif style (FDL) and a woman student with field dependent cognitif style (FDP). The result of the study shows: (1) in understanding step, (2) in devising a plan step, (3) in carrying out the plan step, FIL and FIP students are categorized very good because they had fulfilled two indicators of Polya, and (4) in looking back step, FIL student are categorized very good and student FIP are categorized enough because fulfilled one of the two indicators. for student FDL and FDP 1) in understanding step, (2) in devising a plan step, (3) in carrying out the plan step, FDL and FDP students are categorized very good because they had fulfilled two indicators of Polya, and (4) in looking back step, FDL and FDP students are categorized bad because they had not fulfilled the two indicators.Keywords: Problem Solving, Field Independent, gendre